Football Augmented Reality Media Application for Student Learning Interests - Sulistyo Handayaningrum, Lufita; Mochamad Ridwan (Sekolah Tinggi Olahraga dan Kesehatan Bina Guna, 2023)
Learning by drip with the media is a way of learning that can increase the interest in learning. This learning can be enhanced by applying augmented reality media. The application of augmented reality emphasizes the implementation of learning with a more diverse and interactive virtual concept. The learning dribbling model applied in this study is a direct and indirect learning model with augmented reality. This study aims to achieve the thesis on (1) the influence of the application of augmented reality in soccer ball dribbling equipment on students' learning interests and (2) the increase in students' interest in learning to use augmented reality football dribbling devices. This research method is a pre-empirical design with a quantitative descriptive approach. The study design used was a pre-test-post-test group design. Data collection was carried out using observation, interview and questionnaire techniques. Observation techniques were used to observe the target audience, interviews were used to collect data, while angle distribution was used to determine student interest in learning. The results show that there is an effect of augmented reality media on soccer dribbling material on learning interest of grade VIII-5 students at Junior high school of 1 Nganjuk, expressed as a significance value of 0.000 < 0.05 and student interest in learning in grades VIII-5 at Junior high school of 1 Nganjuk 1 Nganjuk using augmented reality media on soccer dribbling equipment increased to 6.4% when being treated.